Book Reviews: Mikhail Lifshits: In the World of Aesthetics (Moscow: "Izobrazitel'noe iskusstvo" Publishers, 1985, 320 pp.). - Arslanov, V. G. (Russian Studies in Philosophy, 1988)
This book was prepared for publication while the author was still living, but was published two years after his death. All the articles in the book were written between 1969 and 1981, with the exception of short selections that are printed here for the first time.